PERANCANGAN KONTROL ROBOT PEMOTONG RUMPUT - Hutagalung, Jhonson Efendi; Dahriansah, Dahriansah (Riau Journal Of Computer Science, 2019)
To open a new land, it is necessary to clear land from grass plants that surround the land, so we need to cut grass quickly. If you still use traditional equipment, the work will be long and require a lot of workers to complete it. So the author here makes a machine or robot that can later finish cutting the grass quickly and also does not require many workers even though the land is so vast. This robot is controlled by a voice command so that the robot can move in accordance with the commands we take to the smartphone. As long as the robot moves forward, turn, turn left and turn right then the grass cutter knife will spin to cut the grass. The results of this study are a prototype / miniature of a lawn mower robot that has been tried by cutting grass but on a mini scale because it is still the initial model of the system that will be planned to be real for future research